The cenozoic stratigraphy and associated heavy mineral palaeo-placer deposit on Geelwal Karoo : West Coast, South Africa - Elferink, Lisa (Stellenbosch : Stellenbosch University, 2012)
ENGLISH ABSTRACT: The farm Geelwal Karoo is situated some 16km north of the Olifants River mouth on the West Coast of South Africa and hosts fluvial, marine and aeolian deposits of post-Gondwana age. The oldest basal fluvial succession, unconformably overlies Proterozoic and Palaeozoic basement rocks and is in turn capped by aeolianite and littoral packages representing two transgressive cycles. The fluvial channel clay succession is deposited in shallow bedrock-incised channels, has a wedge-shape and is deposited parallel to the present coastline. The flow direction is along the coast and the northwardtapering, angular, poorly sorted basal vein-quartz lag indicates a northward palaeo-flow direction. Less than 1% total heavy minerals (THM) is found in the matrix of these gravel units and the heavy mineral suite is distinguished by zircon, pseudorutile and kyanite. The channel clay unit is dominated by an upper, mediumgrained quartzose sand and kaolin clay facies, which shows advanced post-depositional weathering. The fluvial unit is correlated with the channel clay unit of Hondeklip Bay and a Cretaceous age is proposed for the initial channel incision. The two shallow marine successions have been correlated with the Late Miocene, Early Pleistocene, +30m and +50m packages respectively. These marine sediments were first described by John Pether (1994) in the Hondeklip Bay area and were named according to their transgressive maxima. They are transgressive successions arranged en echelon down the coastal bedrock gradient, from oldest and highest to youngest. The offshore environment of the +50m package consists of fine silty sand, which is moderately sorted. The mineral assemblage is dominated by quartz and the average THM is 18%. The inshore environment is distinguished by a single poorly sorted basal cobble lag which shows an overall fining upward succession. The beachface environment is composed of medium to fine-grained sand, which is moderate to well-sorted. Mineral diversity is greatest in the inshore and beachface environments and the average THM for these two units is greater than 35%. The +30m package has been extensively eroded due to its lower erosion and outcrops were sporadic along the coast. The +30m offshore sediments are recognised by fine sediments with high concentrations of glauconite and organic matter. The inshore environment is distinguished by numerous poorly sorted pebble lags with fining upward successions. Both the inshore and beachface units have higher feldspar concentrations than the corresponding +50m units. The average THM for these two units is less than 3%. The aeolianite unit, which comprises several distinct units, extends over the entire length of the study area and is characterized by calcrete and red bed horizons. Colour variations in the otherwise homogeneous unit are due to heavy mineral enrichment and/or different degrees of in situ weathering and cementation. The unit is composed exclusively of fine- to medium-grained sand and the THM concentration averages 9%. This unit is composed of more than one generation of aeolian sand and forms part of an aeolian transport corridor which transported sand from the beach to the interior. The oldest unit has been equated with the Upper Miocene Prospect Hill Formation, whereas the more recent yellow dune sand is equated with the Pleistocene Springfontyn Formation. At Geelwal Karoo, only the heavy sand placer in the +50m package was deemed to be of any economic significance. The average THM of this placer was calculated to be 40% and some 150 thousand tons of Tibearing material can be expected from this succession. This relatively small volume of heavy minerals and extensive cementation however, make this placer a less attractive prospect than the neighbouring Namakwa Sands operation.